Catchment rainwater and cloud water in the dry season in the city of Xalapa, Veracruz, México - Paulo César Parada Molina; Juan Cervantes Pérez (Ingeniería del Agua)
This paper evaluates the amount of rainwater and fog captured and its relation with average consumption at the dwelling level in the city of Xalapa, Veracruz, Mexico, during the period from November 2012 to February 2013. Rainwater is quantified by means of rocker gauges installed on the roofs of houses and fog through an omnidirectional collector commonly known as a rope collector. It is observed that the amount of rainwater collected monthly can represent 20 to 35% of the average monthly consumption, demonstrating that the rainwater harvesting is an alternative supply to meet domestic needs in the dry season. As for the amount of fog captured its values are low although it should highlight the large amount that the vegetation naturally captures.